GERAKAN ALIGARH DI INDIA (REFLEKSI HISTORIS GERAKAN MODERNISME PENDIDIKAN SAYYID AHMAD KHAN) - Amrullah, Zen (STAI Ma'had Aly Al-Hikam Malang, 2021)
Abstract: The existence of the domination of the western world, especially in the fields of science and technology, has given rise to the awareness of Muslim scientists to escape from this domination. And various efforts were made by Muslim reformers in order to restore the identity of Islam, which then the movement was called modernism, tajdid, ishlah, or renewal. One of the figures who organized this educational modernism movement was Sayyid Akhmad Khan from India with his Aligarh movement called scientific society. The reform made by Sayyid Ahmad Khan is that he puts the ideas of religious thought in the world of education. In addition, he also established educational institutions that can be used by all citizens and operated jointly by Hindus and Muslims. In this educational institution Sayyid Ahmad Khan integrates Islamic education with modern western education, so this has an impact on the western view of Muslims in India getting better